Hybrid Energy Solutions for Sustainable Offshore Oil and Gas Operations: Leveraging Thermoelectric, Solar, and Wind Potential - Hilmi, Erik; Yandri, Erkata; Uhanto, Uhanto; Saiful, Rifki; Hamja, Nasrullah (Heca Sentra Analitika, 2024)
The transition towards sustainable offshore oil and gas operations is increasingly important given the declining conventional energy reserves and growing environmental concerns. This research developed a concept design to enhance sustainability in offshore operations by integrating local solar and wind energy sources. The proposed hybrid system combines solar energy systems and wind turbines with traditional Thermoelectric Generators (TEGs), which have traditionally relied on natural gas. The study found that incorporating these renewable energy sources into the system significantly reduces carbon emissions, lowers dependency on fossil fuels, and improves overall operational efficiency. The main conclusion of this research is that integrating local renewable energy sources into offshore operations mitigates environmental impact, offers long-term cost savings, and enhances energy security. This framework provides practical solutions for the energy sector's transition towards greener, more resilient offshore operations.